Modelling and management of the strain situations in hospital systems using an ORCA approach - Kadri, Farid; Pach, Cyrille; Chaabane, Sondès; Berger, Thierry; Trentesaux, Damien; Tahon, Christian; Sallez, Yves (HAL CCSD, 2013)
International audience Management of patient flow, especially the flow resulting from health crises (exceptional situations) in emergency departments (ED), is one of the most important problems ED managers have to deal with. Emergency departments require significant human and material resources to handle this influx of patients, but these are limited and so the medical and paramedical staff are often confronted with strain situations. To deal with these situations, emergency departments have no choice but to adapt. The main purpose of this paper is to characterize these strain situations and introduce a new framework to model these situations in an emergency department (ED) in order to improve their management by the hospital system. The proposed framework integrates an ORCA (Architecture for an Optimized and Reactive Control) approach to proactively schedule (where possible) the behaviour of a hospital system and to handle strain situations reactively.